2017
DOI: 10.1242/bio.021212
|View full text |Cite
|
Sign up to set email alerts
|

Disruption ofpdgfraalters endocardial and myocardial fusion during zebrafish cardiac assembly

Abstract: Cardiac development in vertebrates is a finely tuned process regulated by a set of conserved signaling pathways. Perturbations of these processes are often associated with congenital cardiac malformations. Platelet-derived growth factor receptor α (PDGFRα) is a highly conserved tyrosine kinase receptor, which is essential for development and organogenesis. Disruption of Pdgfrα function in murine models is embryonic lethal due to severe cardiovascular defects, suggesting a role in cardiac development, thus nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 50 publications
1
16
1
Order By: Relevance
“…The aforementioned "gain-of function" outcome in GBT0419 appears to be different from what have be previously described in other GBT lines, as all have been to date demonstrably loss-of-function mutants (17,20,40,41,69). However, it is still possible that GBT0419 is a loss-of function allele at mRNA or even protein level, given that this mutant has a blunted rxraa response to 9-cis RA (Supplemental Figure 6B, 6C), and the activated RA signaling in GBT0419 could be the consequence of certain 'feed-forward' mechanism that has been previously recognized (47).…”
Section: Discussion Rxraa Is a Therapeutic Gene Target For Dic In Aducontrasting
confidence: 58%
See 1 more Smart Citation
“…The aforementioned "gain-of function" outcome in GBT0419 appears to be different from what have be previously described in other GBT lines, as all have been to date demonstrably loss-of-function mutants (17,20,40,41,69). However, it is still possible that GBT0419 is a loss-of function allele at mRNA or even protein level, given that this mutant has a blunted rxraa response to 9-cis RA (Supplemental Figure 6B, 6C), and the activated RA signaling in GBT0419 could be the consequence of certain 'feed-forward' mechanism that has been previously recognized (47).…”
Section: Discussion Rxraa Is a Therapeutic Gene Target For Dic In Aducontrasting
confidence: 58%
“…In GBT mutants, a monomeric red fluorescent protein (mRFP) gene in the RP2 vector is fused in-frame with the N-terminal part of the affected gene (20), which reports the expression pattern of the trapped gene as a chimeric protein (17,40,41). Because GBT0419 harbors the RP2 element in the 1 st intron of rxraa ( Figure 1A), we documented mRFP expression pattern in GBT0419, and crossed it with Tg(fli1a:EGFP) (42) to label endothelial cells and Tg(ttn:actn-EGFP) (17) to label cardiomyocytes, both with enhanced green fluorescent protein (EGFP), respectively.…”
Section: Endogenous Rxraa Is Expressed In Both Myocardial and Endothementioning
confidence: 99%
“…At the end of this pipeline, 204 GBT-candidate lines met the highest stringency of confirmed expression linkage and were classified as ‘GBT-confirmed lines’ ( Figure 2A ). While 57 of these GBT-confirmed lines have been previously published ( Clark et al, 2011a ; Ding et al, 2013 ; Ding et al, 2017 ; El-Rass et al, 2017 ; Ma et al, 2020 ; Westcot et al, 2015 ), 147 of these GBT-confirmed lines are newly characterized in this manuscript and were selected for confirmation based upon their expression pattern and/or homozygous phenotype ( Supplementary file 1 ). A small subset of these GBT-confirmed lines mapped to areas in the genome without annotated transcripts.…”
Section: Resultsmentioning
confidence: 99%
“…All plots show median. The data of previous protein trap systems were converted from the data in the original articles, R14-R15, our initial R-series protein trap vectors (n = 6), ( Clark et al, 2011a ; FlipTrap, FlipTrap vectors (n = 6), Trinh et al, 2011 ; FT1, FT1 vector (n = 4), Ni et al, 2012 ; RP2.1, RP2.1 vector (n = 26), Clark et al, 2011a ; Ding et al, 2013 ; Ding et al, 2017 ; El-Rass et al, 2017 ; Westcot et al, 2015 and unpublished data) ( Figure 3—source data 1 ). The graph was made in JMP14 (SAS, Cary, NC).…”
Section: Resultsmentioning
confidence: 99%
“…The Tg(Flk1:EGFP) line was maintained and crossed using standard techniques [19]. All zebrafish experiments were approved by the St. Michael’s Hospital Animal Care Committee (Toronto, Ontario, Canada) under protocol ACC867.…”
Section: Methodsmentioning
confidence: 99%